The Low Countries - Rachlis, Eugene; The Editors of Life (Time Incorporated New York, 1963)
Useful information on Holland, Belguin and the Dutch.
Introduction : A unity through diversity : Years of turbulence and revolt : The toppled empires : the Royal Democracies : Out of the Rubble : Masterpieces for a small audience : Water, Water, everywhere : Pride and Provincialism : the Vanishing customs house : A Community of Nations : Appendix : Credits : Index
Includes Index
Keywords: Benelux countries -- Belgium